Clonal evolution patterns in acute myeloid leukemia with NPM1 mutation - Cocciardi, Sibylle (Nat Commun, 2019)
Mutations in the nucleophosmin 1 (NPM1) gene are considered founder mutations in the pathogenesis of acute myeloid leukemia (AML). To characterize the genetic composition of NPM1 mutated (NPM1(mut)) AML, we assess mutation status of five recurrently mutated oncogenes in 129 paired NPM1(mut) samples obtained at diagnosis and relapse. We find a substantial shift in the genetic pattern from diagnosis to relapse including NPM1(mut) loss (n = 11). To better understand these NPM1(mut) loss cases, we perform whole exome sequencing (WES) and RNA-Seq. At the time of relapse, NPM1(mut) loss patients (pts) feature distinct mutational patterns that share almost no somatic mutation with the corresponding diagnosis sample and impact different signaling pathways. In contrast, profiles of pts with persistent NPM1(mut) are reflected by a high overlap of mutations between diagnosis and relapse. Our findings confirm that relapse often originates from persistent leukemic clones, though NPM1(mut) loss cases suggest a second “de novo” or treatment-associated AML (tAML) as alternative cause of relapse.